PARADIGMA TEORI ARENA PRODUKSI KULTURAL SASTRA: KAJIAN TERHADAP PEMIKIRAN PIERRE BOURDIEU - Kukuh Yudha Karnanta (POETIKA, 2013)
This article discusses the concepts of  Pierre Bourdieu’s ideas that integrate literary study, sociology, economics  and politics in the study of  recent literature. Although Bourdieu’s thought began widely introduced into the social -humanities studies in Indonesia, but the application of  these ideas in literary studies in Indonesia are relatively not much done. With Thomas Kuhn’s concept of  paradigm, this article is going to formulate the key concepts in field cultural production which are assumed relevant to explain the dynamics of  contemporary Indonesian literature.Keywords: paradigm, literature, sociology, trajector y, habitus, literar y field, strategy